A Note on Quantum-Secure PRPs - Mark Zhandry (Quantum)
We show how to construct pseudorandom permutations (PRPs) that remain secure even if the adversary can query the permutation, both in the forward and reverse directions, on a quantum superposition of inputs. Such quantum-secure PRPs have found numerous applications in cryptography and complexity theory. Our construction combines a quantum-secure pseudorandom function together with constructions of classical format preserving encryption. By combining known results, we show how to construct quantum-secure PRP in this model whose security relies only on the existence of one-way functions.